The The Relationship Between Diet and Coffee Consumption and the Incidence of Gastritis at Wonoayu Community Health Center - Adin Sania Mufarika; Tanty Wulan Dari; Luluk Widarti; M. Afif Hilmi M. (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
Gastritis is an inflammation of the gastric mucosa that can be caused by various factors, both internal and external, such as irregular eating patterns and excessive coffee consumption. In recent years, the number of gastritis cases in the Wonoayu Community Health Center working area has shown a significant increase. This indicates the importance of preventive efforts by understanding the risk factors that can cause gastritis, especially those related to lifestyle. This study aims to determine and analyze the relationship between diet and coffee consumption with the incidence of gastritis in people visiting the Wonoayu Community Health Center. This study used a quantitative method with a descriptive correlation design and a cross-sectional approach. The population in this study were patients diagnosed with gastritis at the Wonoayu Community Health Center, with a sample of 63 respondents taken using a simple random sampling technique. Data collection instruments were questionnaires and medical record data. Data analysis was performed using the chi-square test with a significance level of p < 0.05. The results showed that the majority of respondents had a diet in the adequate category (63.5%) and coffee consumption in the moderate category (42.9%). The results of the chi-square statistical test showed a significant association between diet and the incidence of gastritis (p = 0.000) and between coffee consumption and the incidence of gastritis (p = 0.000). These findings support previous theories and research suggesting that poor diet and excessive coffee consumption can trigger increased stomach acid production, thereby increasing the risk of irritation of the gastric mucosa and the development of gastritis.